Analysis Of Product Quality, Price And Trust On Consumer Satisfaction At Gunawan Furniture, Langkat Regency - Ema Tanti Yani Sihombing; Yana Diana (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of product quality, price and trust on consumer satisfaction in Gunawan Furniture, Langkat Regency. The research is a creative research using data processing with SPSS version 22. In this study, a population of 180 respondents was used, then using the Slovin formula, a sample of 64 respondents was obtained. The data sources used are primary data and secondary data. The data collection technique uses questionnaires, observations, and interviews. The data analysis techniques are multiple linear regression, classical assumption test and hypothesis test. The results of the study show that product quality has a positive and significant effect on consumer satisfaction in Gunawan Furniture. Price has a positive and significant effect on consumer satisfaction at Gunawan Furniture. Trust has a positive and significant effect on consumer satisfaction in Gunawan Furniture. Product quality, price and trust have a positive and significant effect on consumer satisfaction at Gunawan Furniture. There was a strong correlation between product quality, service quality, and emotional bond with customer satisfaction of 46.8% and the remaining 53.2% could be explained by other variables that were not researched such as promotion, distribution, service and so on.